PENERAPAN PERSEPSI ORANGTUA DALAM MEMENUHI HAK PARTISIPASI ANAK USIA 9-12 TAHUN DI DESA BENA AMANUBAN SELATAN NUSA TENGGARA TIMUR - Lodiana Nitti; Friandry Windisany Thoomaszen (Program Studi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
ABSTRACT Parental perception will affect the fulfillment of children’s participation rights. Fullfilment of children’s participation rights will be fulfilled optimally if parents pay anttention to opinions while providing opportunities for children to make and make decisions about the child’s goals and self-interest. The subjects studied consisted of 5 subjects consisting of father and mother who had children aged 9- 12 years. This study uses qualitative research methods, with data retrieval tools in teh form of interviews, observation and documentation. From the research found data were the subjects do not fulfill the right of participation of children up to the maximum ladder where children’s participation rights range from the first ladder to the third ladder. The first ladder to the third ladder is actually a non- participating ladder. This means that children is manipulated, dominated by parents, there is direct communation and the severity of the parent. The children felt disappointed, sad, and angry with the parents but they still tried to hear and obey the parent’s decision. Children from third and fourth subjects experienced excessive fear to speak to their parent (father). Suggestions for parents to be more caring and fulfill the rights of children’s participation so as not to affect the growth and development of children. Keywords: participation rights, children, parents